Establishment and characterization of six canine hepatocellular carcinoma cell lines - Lee, Ja Young; Bae, Kieun; Kim, Jung-Hyun; Han, Hyun-Jung; Yoon, Hun-Young; Yoon, Kyong-Ah (Frontiers in Veterinary Science, 2024)
Background: Hepatocellular carcinoma (HCC) is the most common malignant liver tumor in dogs. Although surgical resection is a major treatment option for canine HCC, there are no distinct strategies for unresectable tumor subtypes or adjuvant chemotherapy for tumors with positive margins. We aimed to establish and characterize novel HCC cell lines from canine patients. Methods: The cellular morphology, general growth features and tumorigenicity of the established cell lines were evaluated. We also examined the sensitivity of the cell lines to multi-target tyrosine kinase inhibitors (TKIs). Results: We established novel canine HCC cell lines from hepatic tumors and an additional kidney tumor of six canine patients. All cell lines showed colony forming and migratory ability. KU-cHCC-001 and KU-cHCC-001-Kidney, two cell lines exhibiting high epithelialmesenchymal transition characteristics, showed tumorigenicity in xenografted mice. Toceranib, a veterinary TKI that targets vascular endothelial growth factor (VEGFR)/platelet-derived growth factor receptor (PDGFR)/c-kit, effectively inhibited the mitogen-activated protein kinase pathway and induced apoptosis. The established canine HCC cell lines showed greater sensitivity to toceranib than to sorafenib, a first-line treatment for human HCC targeting RAF/VEGFR/PDGFR. Sorafenib showed improved anti-tumor effects when co-treated with SCH772984, an extracellular signal- regulated kinase inhibitor. Conclusion: Our study suggests new therapeutic strategies for canine HCC, and these cell lines are valuable research materials for understanding HCC tumor biology in both humans and dogs.